Consequence Operators and Information Algebras (Communications in Mathematical Research, 2019)
In this paper, the continuity of consequence operators is introduced. Relations between consequence operators and their associated information algebras are mainly explored. It is shown that, for any given consequence operator, the associated information algebra can be directly constructed without any additional conditions. Furthermore, if the consequence operators are continous or compact, then the associated information algebras are continuous or compact.
Keywords: information algebra; consequence operator; continuity; compactness